Pengaruh Motivasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Nafisa Production Di Surabaya - Erni Hariyanie; Widodo Widodo; Ahmad Daengs GS; Diana Zuhro; Retno Susanti (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
This research was motivated by a decline in performance at Nafisa Production in Surabaya. Because Human Resources are central figures in organizations and companies. In order for management activities to run well, companies must have knowledgeable and highly skilled employees and efforts to manage the company as optimally as possible so that employee performance increases. The more employees have high performance, the overall company productivity will increase so that the company will be able to survive in global competition. The purpose of this study was to determine the effect of motivation and work environment on employee performance. Through the questionnaire method by distributing questionnaires to 35 respondents from Nafisa Production employees in Surabaya. Based on data analysis and simultaneous hypothesis testing in this study, it can be seen that motivation (X1) and work environment (X2) simultaneously influence employee performance (Y), this can be proven by the calculated F value (23.380) > F table (2.034) ). Meanwhile, the R multiple value of 0.771 shows that the closeness of the relationship between the independent variable and the dependent variable is 77.10%. While the value of the coefficient of multiple determination is 0.594 which means that all independent variables can explain employee performance (Y) of 59.40%. Partially, motivation affects the performance of Nafisa Production employees. This can be seen from the calculated t value, which is greater than motivation (X1) of 2.918 compared to the work environment variable which is only 2.918. Thus it can be concluded that motivation and work environment have a significant influence on the performance of NAFISA Production Surabaya employees